Cerebral Functional Response during Eyelid Opening/Closing with Bell’s Phenomenon and Volitional Vertical Eye Movements in Humans - Suzuki, Yukihisa; Kiyosawa, Motohiro; Ishiwata, Kiichi; Oda, Keiichi; Ishii, Kenji (The Tohoku Journal of Experimental Medicine, 2016)
Bell’s phenomenon is a physiological phenomenon wherein the eye ball involuntarily rolls upward during eyelid closing. Although this phenomenon occurs in healthy individuals, the neural mechanism related to Bell’s phenomenon has not yet been identified. We aimed to investigate the brain regions relevant to Bell’s phenomenon and volitional eye movement using [15O] H2O and positron emission tomography (PET). We measured regional cerebral blood flow (rCBF) in 8 normal subjects under 3 conditions: at rest with eyes closed, during opening and closing of the eyelids in response to sound stimuli (lid opening/closing), and during vertical movement of the eyes with lids closed in response to sound stimuli (volitional eye movement). The supplementary motor area (SMA) proper, right superior temporal gyrus, right insular cortex and left angular gyrus were activated during lid opening/closing. The right frontal eye field (FEF), pre-SMA, left primary motor area, right angular gyrus, and SMA proper were activated during volitional eye movement. The SMA proper was active during both tasks, while the FEF and pre-SMA were active during volitional eye movement, but not during eyelid opening/closing. A comparison of activation during volitional eye movements and lid opening/closing tasks revealed a relative increase in rCBF in the FEF. There were no areas that are activated in relation to Bell’s phenomenon. In conclusion, activation in the FEF mainly occurs during volitional eye movement. Since Bell’s phenomenon is a reflexive eye movement, the FEF is scarcely concerned in Bell’s phenomenon.